Characterisation of soot in oil from a gasoline direct injection engine using Transmission Electron Microscopy - La Rocca, A.; Bonatesta, F.; Fay, M.W.; Campanella, F. (Elsevier, 2015)
In this work, an investigation of soot-in-oil samples drawn from the oil sump of a gasoline direct injection (GDI) engine was carried out. Soot particulate was characterised in terms of size, distribution and shape of the agglomerates, and internal structure of the primary particles. The test engine was a 1.6l modern light-duty EURO IV engine operated at speed between 1600 and 3700rev/min, and torque between 30and120Nm.After a double oil-flushing procedure the engine was operated for 30h. Oil samples were drawn from the sump and prepared for Transmission Electron Microscopy (TEM) and High resolution TEM analysis (HRTEM) by a combination of solvent extraction, centrifugation and diethyl ether bathing. Soot agglomerates were measured in terms of their skeleton length and width, and fractal dimension. The mean skeleton length and width were 153nm and 59nm respectively. The fractal dimension was calculated using an iterative method and the mean value was found to be 1.44. The primary particles were found to be spherical in shape with some irregularities and presented an average diameter of 36nm with a mode of 32nm and standard deviation of 13nm.The majority of particles showed an inner core and outer shell similar to diesel soot, although an amorphous layer was also clearly visible.